Sharing Our Knowledge Best Practices for Supporting English Language Learners in Schools - Prokopchuk, Nadia; Open Textbook Library (Open Textbook Library, 2019)
To complete the course ECUR 415.3: Current Issues in EAL, students are required to submit a final paper that reflects their growing knowledge about English as an Additional Language (EAL). EAL is the term used in Saskatchewan to describe students who speak languages other than English and require adequate levels of English to be successful with the school curriculum. Most students enrolled in the online course ECUR 415 are practicing teachers who are working toward a Post-Degree Certificate in EAL Education (PDCEAL), while continuing to live and work in various locations both within and outside of the province. The certificate program, offered through the College of Education, University of Saskatchewan, is recognized by provincial education authorities as being equivalent to one full year of post-degree study. As such, the certificate equips teachers with the knowledge and expertise to be considered teacher-specialists of EAL Education. The course ECUR 415 also attracts some pre-service teachers who are pursuing a Bachelor of Education degree and have an interest in EAL Education.
Part 1: Welcoming Environments and Cultural Responsiveness -- 1 - Impact of Culture on EAL Students' Education -- 2 - The Importance of Culturally Responsive Teaching -- 3 - Supporting Newcomer EAL Students in the Elementary Classroom: The First Weeks -- 4 - Teaching EAL Students: Children of Two Language Worlds -- 5 - Culturally Responsive Pedagogy -- 6 - Intercultural Competence and the Inclusive Classroom -- Part 2: Classroom Support for EAL Learners -- 7- Instructional Strategies to Support EAL Learners at Various Stages of the CFR -- 8 - Supporting the Needs of EAL Learners -- 9 - The Power of Visual Notetaking: Empowering EAL Student Learning in the Classroom -- 10 - The Importance of Meaningful and Consistent Assessment Practices -- 11 - Support and Resources for EAL Students and Teachers -- Part 3: Settlement and Refugee Support -- 12 - Integration of Newcomers in Saskatchewan Schools: The Role of Settlement Workers -- 13 - Accessing Academic Language in Math and Science for Refugee Learners -- 14 - Supporting Refugee English Language Learners in Canadian Classrooms -- Part 4: EAL Learners with Special Learning Challenges -- 15 - Trauma and its Impact on Learning -- 16 - Distinguishing Between a Language Acquisition Problem and Learning Challenges in ELL Students -- 17 - Disproportionate Representation of English Language Learners in Special Education
In English.
Description based on print resource
Keywords: Education -- Textbooks; Education, Elementary -- Textbooks; Education, Secondary -- Textbooks; General education -- Textbooks